Stretch : how to future-proof yourself for tomorrow's workplace - Willyerd, Karie; Mistick, Barbara, 1955- (John Wiley & Sons, Inc., 2016)
"You know you can do more with your career. And the future is going to demand more of you. The problem is you are so busy keeping up with the day-to-day that you can't prepare for tomorrow. Stretch: How to Future Proof Yourself for Tomorrow's Workplace gives you the confidence and knowledge you need to achieve your goals in an ever-changing world. Karie Willyerd and Barbara Mistick--established experts and the collective winners of dozens of awards in the field of personal development and learning--offer evidence-based guidance on obtaining the skills you will need to thrive in tomorrow's workplace. Built on solid, global research and dozens of personal interviews with people who have achieved new and inspiring goals, Stretch offers advice, valuable insights, anecdotes, and recommendations to make achieving your goals practical and within reach. If you are like other professionals, your biggest worry is becoming obsolete at work. Shifting technologies, fierce competition among corporations, and recruitment occurring on a global level would give anyone concern. To remain relevant in spite of change, you need to know how to: Learn in any situation Open your thinking to a world beyond where you are now Connect to the people who can help you make your future happen Seek experiences that will prepare you for tomorrow Stay motivated through the ups and downs of a career so you can bounce forward Stretch: How to Future Proof Yourself for Tomorrow's Workplace offers five practices to help you start, enhance, and lengthen your career by anticipating the needs of tomorrow's work environment. Don't become obsolete. Instead, stretch to achieve your potential"--